Additively manufactured lattice structures with controlled transverse isotropy for orthopedic porous implants. (November 2022) - Alaña, Markel; Lopez-Arancibia, Aitziber; Ghouse, Shaaz; Rodriguez-Florez, Naiara; Ruiz de Galarreta, Sergio
Abstract: Additively manufactured lattice structures enable the design of tissue scaffolds with tailored mechanical properties, which can be implemented in porous biomaterials. The adaptation of bone to physiological loads results in anisotropic bone tissue properties which are optimized for site-specific loads; therefore, some bone sites are stiffer and stronger along the principal load direction compared to other orientations. In this work, a semi-analytical model was developed for the design of transversely isotropic lattice structures that can mimic the anisotropy characteristics of different types of bone tissue. Several design possibilities were explored, and a particular unit cell, which was best suited for additive manufacturing was further analyzed. The design of the unit cell was parameterized and in-silico analysis was performed via Finite Element Analysis. The structures were manufactured additively in metal and tested under compressive loads in different orientations. Finite element analysis showed good correlation with the semi-analytical model, especially for elastic constants with low relative densities. The anisotropy measured experimentally showed a variable accuracy, highlighting the deviations from designs to additively manufactured parts. Overall, the proposed model enables to exploit the anisotropy of lattice structures to design lighter scaffolds with higher porosity and increased permeability by aligning the scaffold with the principal direction of the load. Highlights: A semi-analytical model is proposed to design scaffolds with transverse isotropy. Simulations and experiments of the structures are conducted to validate the model. Designed structures can match the stiffness values of various bone sites. Mimicking the anisotropy of bone results in scaffolds with improved biocompatibility.